Lipid Lowering Effect of Methanol Extract of Stem of Musa sapientum (Banana) in Cholesterol Fed Rats (Mugda Medical College Journal, 2025)
Dyslipidemia is a common metabolic disorder in clinical practice that may lead to a number of subsequent diseases including coronary heart disease (CHD), dermatological manifestations, pancreatitis, neurological and ocular abnormalities. An experimental study was conducted in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka, Bangladesh, to investigate the lipid lowering effects of methanol extract of the stem of banana (Musa sapientum) in hypercholesterolemic rats. This study also compared the cholesterol lowering effect of methanol extract of the stem of Musa sapientum (Msmt) with atorvastatin, a lipid lowering agent. In this experiment, total thirty (30) rats were divided into 5 groups. There were 6 rats in each group. Group A served as control group, and received a normal diet and water. Group B received a normal diet, water and cholesterol diet, while Group C received a normal diet, water, cholesterol and Msmt (20 mg/kg/day), Group D received a normal diet, water, cholesterol diet and Msmt (40 mg/kg/day), and Group E received a normal diet, water, cholesterol and atorvastatin (0.18 mg/kg/day). After 14 days, blood samples of rats were collected by cardiac puncture and analyzed to observe the change in cholesterol level in experimental rats. Lipid profile showed that serum TC, LDL, TG levels significantly decreased in both Msmt and atorvastatin along with cholesterol fed Group C, D and E (p